PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN SEBAGAI VARIABEL MEDIASI PADA BENGKEL HONDA DAYA MOTOR PONTIANAK - Marsella B31111186, Marsha (Jurnal Manajemen Update, 2016)
There has an awful lot of business form that moves in services sector, one of them is the repairment workshop. The workshop is required not only to provide a good service, but also to be able to offer a high quality service in order to survive the business. A service company that provides the best service creates a good company image in the customer’s mind which yield from the customer’s satisfaction. The establishment of customer’s satisfaction can build a strong bond between company and its customers that lead to the customer’s loyalty toward the company. The purpose of this research is to find out the correlation of good service, company image, and customer’s satisfaction as well as the correlation od service quality, company image, customer’s satisfaction toward the customer’s loyalty. The population of this research is the customers of Honda Daya Motor Pontianak. There are 100 people as the sample of this study. Those are selected through a purposive sampling technique. Data collection instrument is a set of questionnaire which is later being analyse and interpreted by using a likert scale measurement that is qualified for the validity and reliability of the result. The analytical tools used in this study is the Linear Regression Tiered analysis, then being examined through a  partial test of significance (t-test) with the results variable, service quality and corporate image has a positive and significant influence toward the customer’s satisfaction variable. In addition the service quality variable, corporate image and customer satisfaction has a  positive and significant influence toward customers loyalty variable. Partial test results (test t) interprets from the number of the significance probability of each variable < 0.05 (5%). Keywords: service quality, corporate image, customer satisfaction, customer loyalty